High place phenomenon, obsessive-compulsive symptoms and suicidality - Asgari, Zahra; Naghavi, Azam; Abbasi, Ali; Ertle, Andrea; Wiesmann, Lara; Teismann, Tobias (Frontiers in Psychiatry, 2025)
BackgroundThe high place phenomenon (HPP), referring to a sudden urge to jump when standing in a high place, occurs frequently in both suicidal and non-suicidal individuals. Despite apparent similarities, researchers have not yet examined potential associations with obsessive-compulsive symptoms, nor has the phenomenon been explored in a non-Western society.MethodsThe study comprises two samples of Iranian adults: An online sample including N = 257 participants (54% male; Mage=37.03, SDage= 11.51) and a sample of mobility impaired participants including N = 233 participants (56.2% male; Mage=37.84, SDage= 9.75, range: 18–68 years). All participants filled out questionnaires on experiences with the high place phenomenon, depression, suicidal ideation/behavior, anxiety sensitivity and obsessive-compulsive symptoms.ResultsBetween 39% and 62% of participants reported being familiar with the HPP. In both samples, obsessive-compulsive symptoms showed a significant association with the severity of the phenomenon, even after accounting for depression, suicidal ideation/behavior, and anxiety sensitivity. The presence of the HPP was only associated with obsessive-compulsive symptoms in one of the two samples.ConclusionFindings point to the cross-cultural nature of the HPP. Furthermore, the association between obsessive-compulsive symptoms and the HPP speaks to a conceptualization of the HPP as being part of the phenomenological field of (subsyndromal) OCD symptoms.